1983
DOI: 10.1021/j100235a024
|View full text |Cite
|
Sign up to set email alerts
|

Electronic-to-Vibrational Energy Transfer from I(52P1/2)to I2(25<v<43)

Abstract: Electronic-to-vibrational energy transfer from 1*(5 2P1/2) to 12(25 30. Roughly 2% of the I* dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Since trihalogen molecules have frequently been postulated as intermediates in chemical reactions, [39][40][41][42][43][44][45][46][47][48] we propose that the species giving rise to the fast Cl is the Cl 2¯C l(ad) complex formed at the cold surface as a result of prior partial photodissociation of Cl 2 (ad). A direct spectroscopic evidence for the Cl 2¯C l (Cl 3 ) complex has been provided recently.…”
Section: A Experimentsmentioning
confidence: 99%
“…Since trihalogen molecules have frequently been postulated as intermediates in chemical reactions, [39][40][41][42][43][44][45][46][47][48] we propose that the species giving rise to the fast Cl is the Cl 2¯C l(ad) complex formed at the cold surface as a result of prior partial photodissociation of Cl 2 (ad). A direct spectroscopic evidence for the Cl 2¯C l (Cl 3 ) complex has been provided recently.…”
Section: A Experimentsmentioning
confidence: 99%
“…This conflict could be resolved by recognizing that several vibrational energy transfer collisions would be needed to relax the initially formed 1 2 (X,v-40) to levels that did not have sufficient energy to be dissociated by a collision with O 2 (a) (I,(X, v<20)). Assuming that the vibrational relaxation rate constant measured by Hall et al 17 corresponded to Av=-I transfer, David et al" 9 used kinetic modeling to show that the vibrational cascade process would not be fast enough to impact the dissociation rate for the conditions of Heidner et al's" 6 experiments. With this insight it was concluded that I2t is the vibrationally excited species, and Heidner et al's"6 model I rate constants were adopted for subsequent simulations of COIL devices.…”
Section: The Chain Dissociation Mechanism and Problems With The Identmentioning
confidence: 99%
“…The resulting iodine atoms are rapidly excited t o the spin orbit state, I(2P1/2), by energy transfer. The dissociation then rapidly accelerates as I* replaces O2(a) as the dominate partner for production of 1; [22][23][24]311. This dissociation process removes at least 2, and sometimes as many as 6-18, OZ(a) molecules per dissociated 12 …”
Section: Coil Gas-phase Kineticsmentioning
confidence: 99%